Continuous Subcutaneous Insulin Infusion in Patients With Type 2 Diabetes: A Cohort Study to Establish the Relationship Between Glucose Control and Plasma Oxidized Low Density Lipoprotein. (3rd February 2015) - Megson, Ian L.; Treweeke, Andrew T.; Shaw, Andrew; MacRury, Sandra M.; Setford, Steven; Frias, Juan P.; Anhalt, Henry
Background: Oxidative stress is a detrimental feature of diabetes implicated in the progression of the disease and its complications. The relationship between insulin therapy and oxidative stress is complex. This study tested the hypothesis that improved glucose control, rather than insulin dose, is central to reduced oxidative stress in patients with type 2 diabetes following continuous subcutaneous insulin infusion (CSII).Methods: In this 16-week, multicenter study, 54 CSII-naïve patients with type 2 diabetes (age 57 ± 10 years, HbA1c 69 ± 15 mmol/mol [8.5 ± 1.4%], diabetes duration 13 ± 6 years) treated with either oral antidiabetic agents (OAD) alone (n = 17), basal insulin ± OAD (n = 17), or multiple daily injections (MDI) ± OAD (n = 20) were the evaluable group. Diabetes medications except metformin were discontinued, and 16 weeks of CSII was initiated. Insulin dose was titrated to achieve optimal glycemic control. A plasma marker of oxidative stress relevant to cardiovascular disease (oxidized low density lipoprotein [ox-LDL]) was assessed at baseline and week 16.Results: CSII improved glycemic control (HbA1c −13 ± 2 mmol/mol [−1.2 ± 0.2%]; fasting glucose −36.6 ± 8.4 mg/dL; mean glucose excursion −23.2 ± 6.5 mg/dL, mean ± SE; all P < .001) and reduced ox-LDL (–10.5%; P < .05). The antioxidant effect was cohort-independent ( P > .05), but was significantly more pronounced in patients on statins ( P = .019). The effect of CSII was more closely correlated to improvements in glucose excursion ( P = .013) than to insulin dose ( P > .05) or reduction in HbA1c ( P > .05).Conclusions: CSII induces depression of plasma ox-LDL associated with change in glucose control, rather than with change in insulin dose. The effect is augmented in patients receiving statins.